Sarcasm, Criticism, and Social Commentary: A Speech Act Analysis of Tahilalats Digital Comics - Rahmatika , Wina Riski (Applied Linguistics: Innovative Approaches and Emerging Trends, 2024)
This study examines expressive illocutionary speech acts in Mindblowon's Tahilalats comic on Instagram using a descriptive qualitative research method. The findings identify 122 instances of expressive illocutionary speech acts, which are classified into seven categories: gratitude (24 instances), criticism (116 instances), sympathy (15 instances), praise (16 instances), greetings (21 instances), blaming (9 instances), and apologies (21 instances).  Criticism emerges as the most dominant speech act, reflecting the characteristic use of sarcastic humor and social satire in Tahilalats comics. In contrast, blaming is the least frequent speech act, suggesting a tendency to avoid direct confrontation. This study demonstrates that Tahilalats comics effectively employ expressive illocutionary speech acts to establish emotional connections between characters and readers.